Always expect the unexpected: cystic mediastinal lymphangioma in infants – case report and review of the literature - Tomaszewska, Agata; Rutkowska, Sandra; Jończyk-Potoczna, Katarzyna; Wojsyk-Banaszak, Irena; Mańkowski, Przemysław; Jarmoliński, Tomasz; Wachowiak, Jacek; Derwich, Katarzyna; Zając-Spychała, Olga (Pediatria Polska - Polish Journal of Paediatrics, 2025)
In the paediatric population, mediastinal tumours occur quite often. They include a variety of entities, with different aetiologies. The most common tumours localised in the anterior mediastinum include thymoma, lymphoma, and teratoma. Herein we present the case of an 8-month-old female infant diagnosed with a huge mediastinal solid-cystic tumour causing superior vena cava syndrome. Ultrasonography-guided needle aspiration was performed. The aspirated fluid contained no epithelial cells but many lymphocytes and neutrophils, based on a cytological analysis. The culture of the material revealed Staphylococcus aureus MRSA. In accordance with the antibiogram, the vancomycin therapy was continued. The antibiotic treatment was continued for 6 weeks achieving complete remission of the lymphangioma, which had lasted for one year.